2003
DOI: 10.1007/s10327-002-0006-y
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of rice reflectance for estimating leaf blast severity with a multispectral radiometer

Abstract: Rice reflectance was measured to determine the spectral regions most sensitive to leaf blast infection with a multispectral radiometer. As disease severity increased, reflectance also increased in the 400-500 nm (blue), 570-700 nm (red), and 900-2000 nm regions but decreased in the 500-570 nm and 700-900 nm regions. The increased reflectance in the blue and red regions may be attributed to decreased chlorophyll and carotenoid contents in response to the blast infection. The maximum and minimum reflectance diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 23 publications
5
8
0
Order By: Relevance
“…The greatest difference between severity classes, not surprisingly, was found in the NIR region, near 760 nm. This is similar to that found by Kobayashi et al. 2003, Stone et al.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The greatest difference between severity classes, not surprisingly, was found in the NIR region, near 760 nm. This is similar to that found by Kobayashi et al. 2003, Stone et al.…”
Section: Discussionsupporting
confidence: 92%
“…Both these leaf features are grossly affected within the Mycosphaerella lesions. Our results also concur with Kobayashi et al. (2003) and Carter et al.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Compared with those on leaves, studies connecting with spectral properties of rice panicles are limited. A number of Vis have been tested in rice panicles from the milky ripening stage to harvest (Chen et al, 2006) and have been identified as indicators of rice panicle blast (Kobayashi et al, 2001), or as a potent parameter for leaf blast detection (Kobayashi et al, 2003). Kobayashi et al (2001) suggested Vis for rice blast detection, which followed a decrease in the absorbtion of photosynthetic pigments and changes in the internal structure of rice panicles during senescence.…”
Section: Discussionmentioning
confidence: 99%